An update on health-related quality of life from the PROCLIPI study. (October 2021) - Molloy, Kevin; Jonak, Constanze; Porkert, Stefanie; Knobler, Robert; Guenova, Emmanuella; Fassnacht, Chrstina; Woei-A-Ji, F.J. Sherida H.; Busschots, Anne-Marie; Bervoets, An; Hauben, Esther; Cowan, Richard; Papadavid, Evangelina; et al.
Abstract : Background: Health-related quality of life (HRQoL) is a multi-dimensional concept that focuses on the impact of health status on quality of life. Mycosis fungoides/Sézary syndrome (MF/SS), the prototypical forms of cutaneous T cell lymphoma, are visible cutaneous malignancies with a profound effect of HRQoL. The PROCLIPI study is a multi-national prospective study collecting pre-defined clinical, treatment and quality of life data and began recruiting 2015. Objectives: To provide an update of HRQoL data captured in the PROCLIPI study to date. Methods: HRQoL per study visit was assessed using the Skindex-29 questionnaire and data obtained from the PROCLIPI database together with demographic, clinical, and histologic information. The data was analysed using a combination of descriptive and inferential statistics. Results: To date, 1594 Skindex-29 questionnaires (median 1, min–max 1–9) have been collected from 812 individuals from 33 centres across 16 countries. Respondents included 518 males and 294 females (male:fmale ratio 1.8:1) with a median (IQR) age of 61 (48–71 years). CTCL subtypes included 75.5% with classical MF, 13.2% folliculotropic MF, 0.6% with pagetoid reticulosis and 10.7% Sézary syndrome. 76.3% had early-stage disease and 23.6% had late-stage disease. The number of skindex-29 questionnaires collected per visit included: visit 1 = 569, visit 2 = 325, visit 3 = 254, visit 4 = 186, visit 5 = 109 and visit 6+ = 150. The number of paired observations between visit 1 and visit 2 was 188. Median skindex-29 scores improved between visit 1 and visit 2 for symptoms (p=0.002), emotions (p=0.002) and global scores (p=0.007) but not for functioning (p=0.41). No significant differences were identified in Skindex-29 scores beyond visit 2. Conclusion: The PROCLIPI registry is the most extensive study to date to examine HRQoL in patients with MF/SS. Preliminary analysis of this data has shown an improved HRQoL between visit 1 and visit 2 and for both symptoms and emotions possibly due to effective treatment and education on their disease but plateaus after that. Longitudinal analysis of this data will help to identify individual, disease and treatment characteristics that influence HRQoL changes over time.